A study to assess vaccine wastage in an immunization clinic of tertiary care centre, Gwalior, Madhya Pradesh, India - Tiwari, Ranjana; Dwivedi, Shatkratu; Swami, Piyush; Mahore, Rakesh; Tiwari, Sakshi (International Journal of Research in Medical Sciences, 2017)
Background: Vaccines are one of the most successful and cost-effective health intervention. It becomes imperative that use of vaccine was done through a proper framework of practical decision-making that confers positive health and economic benefits to the society of which Vaccine Wastage was a key factor. The aim of the study is to assess “Vaccine Wastage Rate” and “Wastage Factor” of different vaccines given to beneficiaries in Immunization Clinic and based on the above data, recommend measures to reduce it in the Immunization clinic Methods: The present study was a Record Based Retrospective study carried out in Immunization Clinic in Madhav Dispensary of tertiary center at Gajra Raja Medical College, Gwalior, Madhya Pradesh, India. The data was collected from 1 April 2015 - 31 March 2016. Results: Immunization Sessions were conducted in Immunization clinic during reference period and 7 vaccines BCG, OPV, DPT, Hepatitis B, pentavalent, measles and TT were given. Among individual vaccines, wastage rate and wastage factor in BCG (20.71 and 1.26), OPV (14.65 and 1.17), DPT (15.6 and 1.18), Hepatitis B (10.56 and 1.12), Pentavalent (5.2 and 1.05), Measles (21.68 and 1.28), TT (7.09 and 1.08), and IPV (10.49 and 1.12) was respectively. Conclusions: Vaccine wastage could be expected in all programmes and there should be an acceptable limit of wastage. Innovative techniques to be developed not only to reduce wastage but also the operational cost for convenience of children who were to be vaccinated and parents who bring their children for vaccination without compromising coverage.